Peritoneal and extraperitoneal relapse after previous curative treatment of peritoneal metastases from colorectal cancer: What survival can we expect?. (September 2018) - Gelli, Maximiliano; Huguenin, Janina F.L.; de Baere, Thierry; Benhaim, Léonor; Mariani, Antoine; Boige, Valerie; Malka, David; Sourouille, Isabelle; Ducreux, Michel; Elias, Dominique; Goéré, Diane
Abstract: Introduction: Over the last 20 years, complete cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) dramatically increased the survival of patients with colorectal peritoneal metastases (CRPM). However, despite better knowledge of the disease, around 70% of patients relapse after CRS with HIPEC. This study was designed to analyse the pattern of recurrence and the outcomes of different treatment modalities. Methods: Patients relapsing after CRS plus HIPEC for CRPM were selected from a prospective database. The impact of iterative curative-intent treatments was analysed using Kaplan–Meier estimates and multivariate Cox regression models. Results: Between April 1993 and December 2014, 190 of 274 (69%) patients previously treated by CRS plus HIPEC developed relapse, as an isolated peritoneal recurrence (31%), isolated distant recurrence (35%), or multisite recurrence (34%). The curative-intent treatment rate was 48% for isolated peritoneal recurrences, 49% for isolated distant recurrences and 22% for multisite recurrences (p = 0.002). From the diagnosis of relapse, 3- and 5-year overall survival were 77% and 46% after curative-intent treatment and 14% and 4.7% after non-curative treatment, with median survival of 59.7 and 18.3 months (log-rank p < 0.0001), respectively. Regression analysis identified the initial extent of CRPM (hazard ratio [HR]: 2.25; p < 0.0001), iterative curative-intent treatment (HR: 0.22; p < 0.0001) and disease-free interval (HR: 1.77; p = 0.01) as independent predictors of prolonged survival. Conclusions: Iterative curative-intent treatment can be performed in up to 40% of patients with relapse after CRS and HIPEC for CRPM, and is associated with prolonged survival in selected patients. Highlights: About three quarter of patients relapsed after curative treatment of colorectal peritoneal metastases. Relapses were isolated peritoneal (31%), isolated distant (35%) or multisite (34%) metastases. Multimodal strategies and patients' selection yielded to an iterative curative-intent treatment in 40% of patients. Five-year overall survival after iterative curative treatment was 46%, similarly to that obtained in the same scenario from colorectal liver metastases, despite an aggressive recurrent disease.